PROSPECTIVE RANDOMIZED EVALUATION OF THE IMPACT OF MULTIMODAL ANALGESIA AND TRANEXAMIC ACID ON POSTOPERATIVE PAIN AND BLOOD LOSS IN KNEE ARTHROPLASTY PATIENTS - RAZA, SA; SAIFULLAH, .; MINHAS, NM; HAIDER, SI; BAJWA, SH; AHMAD, S; ASHRAF, U; AZAM, W; MASOOD, F; IQBAL, M (Biological and Clinical Sciences Research Journal, 2024)
The most prevalent type of arthritis and a major contributor to disability is osteoarthritis. One of the most successful surgical treatments is total knee arthroplasty (TKA), which improves function and relieves pain in most patients. Objectives: The aim of this study is to evaluate the effects of intra-articular tranexamic acid and multimodal cocktail on postoperative blood loss and pain in patients undergoing total knee replacement. Methods: Enrolled were ninety-six male or female individuals with knee osteoarthritis who intended to have a total knee replacement. Group A received conventional anaesthetic medications only; tranexamic acid was not administered. Patients in Group B received an intraarticular injection of tranexamic acid weighing three grammes. Patients in Group C received a multimodal cocktail consisting of bupivacaine, tramadol, and ketorolac. Following TKA, patients had a 72-hour follow-up period. For 72 hours, blood loss and a pain score were recorded every 24 hours. Results: Patients in the cocktail group were 50.22±9.63 years old, those in the TXA group were 52.31±14.69 years old, and those in the control group were 48.92±13.22 years old. In three groups, the male-to-female ratios were, respectively, 11:21, 14:18, and 10:22. Within the first 72 hours, the control group lost 1030.1±177.27ml of blood, the TXA group lost 453.7±80.4ml, and the cocktail group lost 607.7±122.5ml. There was a significant difference (p<0.05) between TXA and cocktail groups and in all three groups. In the control group, the mean postoperative pain score was 4.4±2.3, in the TXA group it was 2.4±1.5, and in the cocktail group, it was 1.8±1.0 over the first 72 hours. The TXA and cocktail groups showed negligible differences (p>0.05), whereas the three groups showed substantial differences (p<0.05). Conclusion: Compared to the control group, the use of an intraarticular TXA injection was found to be effective in lowering blood loss. Although the multimodal cocktail allowed for better pain management than the other two groups.